TINJAUAN YURIDIS TRANSFORMASI KONSTITUSI INDONESIA - La Ode Muhammad Iman Abdi Anantomo Uke (Al-'Adl, 2019)
The term Constitution comes from the French language (constitution) which is forming, which means the formation of a State or composing and declaring a State. Another term is constitution (English) or gronwet (Dutch) which means the Constitution. According to Sri Soemantri in his dissertation, there is not a single country in the world today that does not have a constitution or constitution. Indonesia is a country that has a constitution as the basis of the state. The constitution in a country always changes according to the times. In Indonesia, the history of constitutional development has changed several times, so that other legislation that is inferior must also change. Therefore, the transformation of the Indonesian state constitution can be judicially reviewed to see the development of the constitution which began in 1945.